2013
DOI: 10.1038/sc.2012.178
|View full text |Cite
|
Sign up to set email alerts
|

Immediate effects of obstacle crossing training in independent ambulatory patients with spinal cord injury

Abstract: Study design: A 2 Â 2 cross-over design. Objectives: To compare immediate effects of obstacle crossing training and conventional overground walking training on functional ability among independent ambulatory patients with spinal cord injury (SCI). Setting: A tertiary rehabilitation center, Thailand. Methods: Twenty independent ambulatory participants with SCI received a 1-day overground walking training and a 1-day obstacle crossing training program in a randomized cross-over design with a 2-day washout period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…This occurs because the SCIM III scores more levels of locomotion and transference, even when the individual already performs this task without any help. It is noteworthy that despite being the standard instrument for functional evaluation of individuals with spinal cord injuries, the FIM TM shows a ceiling effect that can be overcome by measuring gait with other instruments 19 . However, for tetraplegic individuals, the difference is at the lower extremity of the curve, where the SCIM III can perceive variations for lower scores even if the individual has the lowest FIM TM score, because only the SCIM III evaluates breathing, which can be severely compromised in persons with these levels of spinal cord injury, compromising their inhaling and coughing independently or even with the use of ventilators 20 .…”
Section: Discussionmentioning
confidence: 99%
“…This occurs because the SCIM III scores more levels of locomotion and transference, even when the individual already performs this task without any help. It is noteworthy that despite being the standard instrument for functional evaluation of individuals with spinal cord injuries, the FIM TM shows a ceiling effect that can be overcome by measuring gait with other instruments 19 . However, for tetraplegic individuals, the difference is at the lower extremity of the curve, where the SCIM III can perceive variations for lower scores even if the individual has the lowest FIM TM score, because only the SCIM III evaluates breathing, which can be severely compromised in persons with these levels of spinal cord injury, compromising their inhaling and coughing independently or even with the use of ventilators 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Following the first training session, participants went through a 2-day washout period. 9 Confirmation that carryover effects did not occur was established by Grizzle method 9 and data from 10 pilot cases. On the fifth day, participants were involved in the other training program.…”
Section: Interventionmentioning
confidence: 99%
“…The sample size calculation indicated that each training program required 22 participants. A 10-Meter Walk Test (10MWT) was set as a major outcome of the study, and the study used the magnitude of effect sizes from a recent study 9 (μ1 -μ2 = 0.10, σ = 0.09, α = 0.05, and β = 0.10). The inclusion criteria were an age of at least 18 years old, a body mass index between 18.50 and 29.90 kg/m 2 , and a motor incomplete lesion (American Spinal Injury Association Impairment Scale [AIS] C and D) from trauma or nonprogressive disease with a postinjury time of at least 12 months.…”
Section: Participantsmentioning
confidence: 99%
See 2 more Smart Citations